Do Women on Boards Influence Climate Change Disclosures to CDP? – Evidence from Large Indian Companies - B. Charumathi; Habeebu Rahman (Australasian Accounting, Business and Finance Journal, 2019)
Participation of women on corporate boards is increasing across the globe. Corporate with women directors on their board are more likely to address the emerging strategic issues of climate change, enhance GHG emission disclosure strategy and communicate the actions to the stakeholders. According to Board Capital Theory, the presence of women on boards increases board capital breadth in different dimensions. According to Critical Mass Theory, boards with three or more female directors tend to influence the board’s decision-making process which results in more favourable environmental disclosure. Findings of earlier studies reiterate that female executives and directors bring different ethical values and traits to decision-making. This paper studies the effect of women on board on climate change reporting to the Carbon Disclosure Project (CDP) by the large Indian companies. The sample for this study includes S&P BSE 100 indexed companies and the period of the study is 6 years ranging from 2010-11 to 2015-16. This study used secondary data. The CDP data and financial data are taken from Bloomberg Professional Database. Based on the items disclosed by companies for CDP questionnaire, a Carbon Disclosure Index is constructed and used in this study. Using a multiple regression model, it is found that there is a significant positive relationship between the percentage of women directors on boards and climate change-related disclosure to CDP. Using independent ‘t’ tests, it is found that companies having at least three women directors disclose more. Thus, this study supports both board capital theory and critical mass theory.
Keywords: Carbon Disclosure Project; Women on Board; Board Capital Theory; India; Critical Mass Theory; BSE 100 companies.